Hubungan Body image, Tingkat Konsumsi Energi, dan Tingkat Konsumsi Lemak dengan Kejadian Gizi Lebih pada Remaja Putri di SMAN 1 Krian Sidoarjo - Civana Dea Alnanda; Bambang Wirjatmadi (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The incidence of overweight (overweight and obesity) is a nutritional problem caused by excess fat tissue in the body. Adolescent have a high risk of overweight which needs to be considered because it can affect the process of growth and development. The incidence of overweight in female adolescents can be influenced by several factors such as body image, energy intake, and fat intake. The purpose of this study was to analyze the relationship between body image, , energy intake, and fat intake with the incidence of overweight in female adolescents of SMAN 1 Krian.This research is analytic observational research with case control research design. There was a sample of 58 female adolescents who were divided into two groups, in which the overweight and normal nutrition groups consisted of 29 each. Research data obtained from anthropometric measurements, questionnaires, and interviews. Samples were selected randomly using simple random sampling. Research analysis using chi square test and fisher's exact test.The results showed that there was a significant relationship between energy intake (p=0.000) and fat intake (p=0.003) with the incidence of overweight. Meanwhile, between body image (p=0.066) were not there is a relationship with the incidence of overweight.The conclusion of this study is that excess intake of energy and fat can lead to overweight in female adolescents. female adolescents should be given knowledge of the importance of adopting a healthy lifestyle that of eating intake in accordance with balanced nutrition.